Association of initial COVID‐19 vaccine hesitancy with subsequent vaccination among pregnant and postpartum individuals. (19th May 2022) - Germann, Katherine; Kiefer, Miranda K.; Rood, Kara M.; Mehl, Rebecca; Wu, Jiqiang; Pandit, Radhika; Lynch, Courtney D.; Landon, Mark B.; Grobman, William A.; Costantine, Maged M.; Venkatesh, Kartik K.
Abstract: Objective: To examine the association between initial COVID‐19 vaccine hesitancy and subsequent vaccination among pregnant and postpartum individuals. Design: Prospective cohort. Setting: A Midwestern tertiary‐care academic medical center. Individuals completed a baseline vaccine hesitancy assessment from 22 March 2021 to 2 April 2021, with subsequent ascertainment of vaccination status at 3–6 months follow‐up. Methods: We used multivariable Poisson regression to estimate the relative risk of vaccination by baseline vaccine hesitancy status, and then characteristics associated with vaccination. Main outcome measures: Self‐report of COVID‐19 vaccination, and secondarily, consideration of COVID‐19 vaccination among those not vaccinated. Results: Of 456 individuals (93% pregnant, 7% postpartum) initially surveyed, 290 individuals (64%; 23% pregnant, 77% postpartum) provided subsequent vaccination status (median = 17 weeks). Of these 290 individuals, 40% (116/290) reported COVID‐19 vaccine hesitancy upon enrolment, of whom 52% reported subsequent vaccination at follow‐up. Few individuals transitioned during the study period from vaccine hesitant to vaccinated (10%); in comparison, 80% of those who were not vaccine hesitant were vaccinated at follow‐up (aRR 0.19, 95% CI 0.11–0.33). Among those who remained unvaccinated at follow‐up, 38% who were vaccine hesitant at baseline were considering vaccination, compared with 71% who were not vaccine hesitant (aRR 0.48, 95% CI 0.33–0.67). Individuals who were older, parous, employed and of higher educational attainment were more likely to be vaccinated, and those who identified as non‐Hispanic black, were Medicaid beneficiaries, and were still pregnant at follow‐up were less likely to be vaccinated. Conclusions: COVID‐19 vaccine hesitancy persisted over time in the peripartum period, and few individuals who reported hesitancy at baseline were later vaccinated. Interventions that address vaccine hesitancy in pregnancy are needed. Tweetable abstract: COVID‐19 vaccination hesitancy among pregnant and postpartum individuals persists over time, and few of the individuals who reported hesitancy were later vaccinated.